PARTISIPASI MASYARAKAT PADA PILKADA KABUPATEN KARIMUN TAHUN 2015 - M. Rizwan; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to determine the level of correlation of socio-economic status to the political participation of the community of Sungai Lakam Barat Village in the General Election of Head and Deputy Regional Head of Karimun Regency in 2015 and also to find out the inhibiting factors and supporting factors of voting. The design of this study is quantitative where it uses a non probability sampling approach. The data collection technique used was questionnaire sheets which were submitted to the respondents. The analysis used is quantitative analysis which is presented in table form and then explained. Based on the results of this research, the socio-economic status influences the political participation of the Sungai Lakam Barat District Community in the 2015 General Election and Deputy Head of Karimun Regency and the most influential inhibiting factors for voting are loss of trust in politics, and the most influential contributing factor to voting is having an awareness of responsibility as a good Indonesian citizen Keywords: Participation, Politics, and Social Economy